As "mulheres de azul" da Academia Feminina de Letras e Artes de Goiás: trajetórias, (res) existências e estratégias de intelectuais e artistas goianas (1969-1993) - Maia, Débora de Faria (2021)
The present research is a historical study about the Goiás Feminine Academy of Letters and Arts (AFLAG) and its women, founded in 1969, in Goiânia. We will emphasize the trajectory of the writer and intellectual Maria do Rosário Fleury (1913-1993) (Rosarita Fleury), creator of this initiative, which brought this group together and organized it institutionally. For this, through a discursive analysis, our theoretical and methodological contribution is found in the authors: Joan Scott (1995), through the gender category, Michel Foucault (1996, 2014, 2018, 2019) and his definitions of power and speech, together with Pierre Bourdieu (1989, 2004, 2018) to understand the intellectual field and the canon. Our sources are: the Yearbooks, Statutes, Minutes and Reports between 1969 and 1993 produced by the institution, separate newspapers of the time and interviews collected among the women of the founding staff. Gender discourses and constructions consolidated “places” for “male” and “female”, producing hierarchies and legitimizing sexist practices that invalidated women's artistic and intellectual production. Institutions such as the Academia Brasileira de Letras (1897) and Academia Goiana de Letras (1939) are structured before society based on these same discourses and practices, as they did not accept women in their staff. That said, these women from Goiás are claiming a space for recognition and self-affirmation as intellectuals and artists, (re) negotiating places and attributing other meanings to their existence, for this purpose, strategies and alliances were consolidated in order to circumvent and resist barriers of the deeply masculine intellectual state of Goiás. Emphasizing the resistance and existence of these women helps to promote more inclusive and democratic public policies and social practices.